(untitled) (Atlas Journal of Biology, 2017)
Soybean (Glycine max (L.) Merr.) suffers yield losses due to root infection from soil infestation by Heterodera glycine I. (soybean cyst nematode SCN) and Fusarium virguliforme (Aoki; sudden death syndrome (SDS)). The major resistance locus was the Rhg1/Rfs2 region (chr18; LG G). The aim here was to compare Sanger DNA sequence of a resistant (‘Forrest’) and two susceptible cultivars (‘Williams 82’ and ‘Asgrow A3244’). Used were sequences downloaded from GenBank (Williams 82), Phytzome (A3244) and a newly sequenced BAC-B73P06 (82,157 bp) encompassing the resistant Rfs2/Rhg1 locus. Identified were 800 SNPs and 57 indels. In contrast the susceptible cultivars had just 12 SNPs and no indels between them. Polymorphisms were clustered within 59 kbp, divided in three sections. There were 5 predicted recombination breakpoints. The third and fourth breakpoints were located before gene 3 and after gene 5 (Glyma18g02680; the RLK at Rhg1/Rfs2) which were therefore inferred to be Peking derived DNA within Rhg1/Rfs2 region. Comparisons of single nucleotide polymorphisms (SNPs) identified in Illumina sequences from 31 semi-domesticated genomes showed 80% of the total SNPs in Forrest were found among the genomes. Annotation and gene prediction showed the BAC gene prediction encoded 9-10 genes. There were 31 SNPs within exons and 137 among introns. Just 11 SNPs caused amino acid changes. There were 5 SNPs in CREs and 14 in promoters. Polymorphisms indicated the regions that were introgressed from Peking had defined limits. Proteins across the region were highly conserved compared to non-coding regions so infer purifying selection occurred.